(untitled) (World Science, 2021)
In our work, the aim was to conduct a fundamental study of the issue concerning the ultrastructural characteristics of the mucous membrane and cartilaginous corset of the rat larynx in the norm. This information in the future will make it possible to form a base that will be used to compare the components of the mucosa and laryngeal cartilage in the norm with the dynamics of their changes as a result of experimental opioid exposure.